مهارة القراءة وتعليمها ومؤشراتها - Penny Respati Yurisa (Postgraduate of IAIN Metro Lampung Indonesia, 2019)
Reading is a verbal linguistic skill, which includes the identification and understanding of printed symbols, and it is a complex process similar to all processes, requiring understanding, linking, and conclusion by communicating with readers. This article has four goals; to find the goals of reading education, to explain the two types of reading, to determine the assessment of reading skill, and to find the steps of teaching reading skills. This article used library research, the data in the form of literature and analysed without using statistical techniques. First, one of the goals of reading education is the ability of students to find new ideas and knowledge. Second, that there are two types of reading. The first type is silent reading, and the second type is aloud reading. Third, assessment of reading skill in a general characteristic consists of two aspects, namely pronunciation and comprehension. Fourth, the teaching of reading skills has the following steps: Providing readable texts for students to read in secret or in public, appropriate for the available study times. Dialog about the content of the read. When the teacher wanted to explain the rules, the teacher does the shortest explanation, because the focus in teaching reading is to provide read texts, and read them secretly or publicly. The teacher provides an explanation of difficult vocabulary, or problem terms in students. At the end of the meeting, the teacher gives assignments about the content of the reading, such as summarizing the material, assigning the subject, or other assignments.